Kepercayaan Eksistensial Mahasiswa Ditinjau Dari Latar Belakang Pendidikan dan Pendidikan Orang Tua: Studi Terhadap Mahasiswa Prodi PGRA - Ichsan, Ichsan (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2015)
This research has two objectives: First, to determine differences in student existential belief between students coming from high school and Madrasah Aliyah. Second, to determine differences in student existential belief according to educational level of parents of students. The hypothesis of this study: First, there is no differences in student existential belief between students coming from high school General and Madrasah Aliyah (MA). Second, there is no differences in student existential belief overview on parent education students are low, medium and high. The respondent in this study is students of PGRA class 2013/2014 and 2014/2015 totaling 126 students. Data collection tools that are used include: belief scale questionnaires adapted from C. Asri Budiningsih, Parent Education Level questionnaires, and documents. comparison test results using analysis of variance (ANOVA) two lanes obtained the values of F : 0,034 for the first hypothesis, and the value of F: 0.496 for the second hypothesis. based on the results of statistical tests can be concluded: first, there is no difference in existential belief between students from high school (SMA / SMK) and Madrasah Aliyah (MA). Secondly, there is no difference in the existential belief that the student has a parent (father) with a higher education level, medium and low.